Bewilderment [large type] : a novel - Powers, Richard, 1957- (Thorndike Press large print core, 2022)
"The astrobiologist Theo Byrne searches for life throughout the cosmos while single-handedly raising his unusual nine-year-old, Robin, following the death of his wife. Robin is a warm, kind boy who spends hours painting elaborate pictures of endangered animals. He's also about to be expelled from third grade for smashing his friend in the face. As his son grows more troubled, Theo hopes to keep him off psychoactive drugs. He learns of an experimental neurofeedback treatment to bolster Robin's emotional control, one that involves training the boy on the recorded patterns of his mother's brain...With its soaring descriptions of the natural world, its tantalizing vision of life beyond, and its account of a father and son's ferocious love, Bewilderment marks Richard Powers's most intimate and moving novel. At its heart lies the question: How can we tell our children the truth about this beautiful, imperiled planet?"--